(untitled) (Herald of the National Children’s Medical Center, 2025)
Infected echinococcal cysts (EC) of the lungs in children often complicate with rupture into the bronchi and pleural cavity, which worsens the course of the disease and increases the risk of postoperative complications. The relevance of this problem is due to the necessity of developing and implementing effective surgical and conservative treatment methods aimed at minimizing the frequency of complications and recurrences.